Impact of Social Media Advertising and Brand Ambassadors On 3Second Brand Awareness - Hamka, Ahmad; Aqsa, Muhammad; Rahmawati, Rahmawati (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the impact of social media advertising and brand ambassadors on brand awareness. The background of this research is based on the increasing competition in the local fashion industry and the role of social media as the main platform in modern marketing. Methodology: The research method used is a quantitative approach with multiple linear regression analysis techniques. The research sample consisted of 110 students of class XII IPS at SMAN 1 North Luwu, which was selected using the saturated sample method. Data were collected through questionnaires and analyzed using statistical techniques to test the relationship between independent variables (social media avertising and brand ambassadors) and dependent variables (brand awareness). Results: The results showed that social media advertising has a positive and significant influence on brand awareness, which is indicated by a t-value of 6.349 and a P-value of 0.000. In addition, brand ambassadors also have a significant influence on brand awareness with a t-value of 8.646 and a Pvalue of 0.000. Simultaneously, the two variables explain 72.5% of the variation in brand awareness, indicating that the combination of digital marketing strategies through social media advertising and the use of brand ambassadors is an effective approach to increase brand awareness of 3 Second product. Findings: This research emphasizes the importance of effective strategies using social media advertising, and the use of brand ambassadors plays a major role in strengthening brand positioning in competitive markets, especially in the fashion industry targeting the younger generation. Conclusion: The results showed that advertising on social media and the use of brand ambassadors played a major role in increasing 3Second's brand awareness. These two strategies together affect 72.5% of the increase in brand awareness. The main factors that make this strategy effective are the attractive appearance of advertisements, how often advertisements appear, and the popularity of brand ambassadors such as Raffi Ahmad, who successfully increase consumer interest and encouragement to buy products. Type of Paper: Empirical Reasearch Paper